Insights to the formation of secondary inorganic PM2.5: Current knowledge and future needs - Wang-Li, Lingjuan (International Journal of Agricultural and Biological Engineering, 2015)
As a criteria pollutant, fine particulate matter (fine PM, i.e. PM2.5) adversely affects public health and environment, contributes to visibility degradation and regional haze. Atmospheric fine PM includes primary and secondary PM2.5. While the primary PM2.5 is from direct emissions, the secondary PM2.5 is formed in the atmosphere through photochemical reaction, condensation and other atmospheric processes. Although it is well known that ammonia (NH3) may react with acidic gas species to form secondary inorganic PM2.5 (iPM2.5) as ammonium salts, limited research has been done to quantify the impacts of NH3 emissions of animal feeding operations (AFOs) on the dynamics of such chemical reactions and gas-particle phases partitioning. This paper is to provide comprehensive review of existing research on AFO PM chemical speciation and on the formation of secondary iPM2.5 as impacted by AFO air emissions. Research gaps and future studies in characterizing AFO PM and assessing impacts of AFO air emissions on atmospheric PM are discussed. Keywords: environmental pollution, particulate matter, inorganic PM2.5, animal feeding operations, ammonia, formation of secondary PM2.5 DOI: 10.3965/j.ijabe.20150802.1810